Determinants of Service Exports in Saudi Arabia Using Factor Analysis - Mohamed, Nashwa; El-Tayeb, Manahil (Jordan Journal of Economic Sciences, 2019)
The objective of the present study is to determine the factors affecting the growth of services exports in Saudi Arabia during the period 1975-2014; due to the low importance of these exports in GDP compared to their increasing importance globally. The research methodology, for achieving this goal, was based on the method of Factor Analysis, which allowed the inclusion of a large number of independent variables after reduction, in the Linear Multiple and Stepwise regression models to explore the most important determinants, whereas previous studies limited the analysis of fewer factors using other statistical methods and different applied scope. The results have concluded to the positive impact of financial development, domestic investment, value added for agriculture and services, as well as the development of human capital and telecommunications infrastructure. It also found the negative impact of oil revenues and domestic savings on service exports. In terms of the relative importance of the determinants, the results indicated that the development of human capital and financial development were the most important.